Prevalência e distribuição da infecção pelo Mycobacterium leprae por meio de marcadores sorológicos e geoprocessamento em Diamantina, Minas Gerais - Gabriela de Cássia Ribeiro (2019)
The measures established today for the control of leprosy in Brazil still offer slow answers in practical terms, which leads one to believe that, even if the country reaches the goal of elimination as a public health problem, neglect of actions can keep it in the situation of endemic. Serological tests may be of great value in identifying population's exposure to leprosy. Spatial analysis may provide a great deal of information on the transmission pattern of the disease or Mycobacterium leprae infection. The objective of this study was to analyze the use of serological markers and spatial analysis to estimate the prevalence of Mycobacterium leprae infection in order to broaden the scope of epidemiological surveillance actions of leprosy. This is a cross-sectional, descriptive and analytical study carried out in the municipality of Diamantina, located in Vale do Jequitinhonha / MG, Brazil. It was composed of 3 populations, being: population 1 - cases reported from 2001 to 2014 and contacts of leprosy; population 2 - schoolchildren aged 7 to 14 enrolled in state schools in the municipality and population 3 - relatives and neighbors of seropositive schoolchildren and neighbors of leprosy cases. Interviews, dermato-neurological examination and serological tests were performed. The addresses were geo-referenced. The cases of seropositive leprosy resided in the rural zone (p = 0.016), with more people at home (p = 0.009) and slept with at least one other person (p = 0.023). Seropositive leprosy contacts were statistically significant with serology in relation to the age group, with the majority of elderly individuals (p = 0.038) and 75.0% being spouses of the cases (p = 0.035). Among the seropositive schoolchildren, there was statistical relevance for gender (p = 0.032), in which the majority were girls (75.0%), BCG scar (p = 0.005) where almost all were vaccinated (94.4%), and 69.4% lived with more than 4 people at home (p = 0.027) and 80.6% shared the room with another person (p = 0.043). For the population 3, there was more chance of having positive serology among the younger (p <0.001) and contradictorily among the widows of this sample (p = 0.041); (p = 0.007), with a family income of around one minimum wage (p =0,002), who did not have chronic disease (p = 0.012) and had no skin blemishes (p = 0.034). In the spatial analysis, hyper endemic areas and areas with positive local spatial association (p = 0.001) with high (high-high) and low (low-low) detection rates are observed. There was a space-time relationship between the cases diagnosed with 03 years of difference and residents within the 100-meter radius (p = 0.01). The concentration of seropositive cases and schoolchildren occurred in areas with lower per capita family income, and the areas of positive serology concentration differed from clusters of illness (p <0.001). Conclusion: The research has an innovative character combining two techniques to subsidize the epidemiological surveillance of leprosy in a medium endemicity municipality. Serological tests were able to indicate the active transmission chain and the spatial analysis of the endemic distribution pattern in the municipality, facilitating the planning of prevention actions by management. Studies using samples from all census tracts in the municipality and longitudinal are suggested in order to follow the seropositive participants and to monitor the hidden prevalence of leprosy.